The Ethical Crossroads: Does AI in Healthcare Respect Religious and Spiritual Beliefs? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
The Ethical Crossroads: Does AI in Healthcare Respect Religious and Spiritual Beliefs? The integration of Artificial Intelligence (AI) into healthcare p...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical AI